On Becoming a Change Agent: Journeys of Teaching Gender and Health in an African Crisis Context - Musa W. Dube (Journal for Interdisciplinary Biblical Studies, 2020)
This paper discusses my activities in the classroom and beyond to address African contexts of the HIV and AIDS crisis. Alongside an account of my strategies, encounters and journeys, I discuss the activist Gugu Dlamini and Mmutle, a trickster of African folklore. Both act as inspirations for the role of change agent.